Enhancing Students’ Learning Motivation through Changing Seats in Primary School - Hardiansyah, Framz; AR, Muhammad Misbahudholam (Universitas Pendidikan Indonesia, 2022)
The problem that teachers often face in primary school is the students’ low absorption in understanding a lesson. Currently, learning is still teacher-centered, which causes students to be less active in participating in the teaching and learning process. The problem in this research is how to enhance students' learning motivation through changing seats in primary school. This study is a quantitative study with a research design using a post-test-only control design. The data were collected using test and observation method and were analyzed using normality test, homogeneity test, t-test, and further hypothesis testing, which is to compare the learning outcomes of the experimental class and the control class. This study concludes that there was an increase in students' learning motivation through changing seats in primary schools, which can be seen from the results of data analysis showing that the value of tcount = greater than ttable = 2.2899 at a significant level of 5% (tcount ttable ) count 3.0030 table 2.2899, H0 was accepted.